Adaptations of Vibrio parahaemolyticus to Stress During Environmental Survival, Host Colonization, and Infection - Pazhani, Gururaja Perumal; Chowdhury, Goutam; Ramamurthy, Thandavarayan (Frontiers in Microbiology, 2021)
Vibrio parahaemolyticus (Vp) is a halophilic, aquatic Gram-negative bacterium that may infect humans and cause gastroenteritis and wound infections. The first pandemic of Vp associated infection was caused by the serovar O3:K6 and epidemics caused by the other serovars are increasingly reported. The two major virulence factors, thermostable direct hemolysin (Tdh), and/or Tdh-related hemolysin (Trh) are associated with hemolysis and cytotoxicity. Vp strains lacking tdh and/or trh are avirulent and do not colonize in the human host. This pathogen is well adapted to survive in the environment and human host using several genetic mechanisms. The presence of prophages in Vp contributes to the emergence of pathogenic strains from the marine environment. Due to differential expression, type III secretion system 2 (T3SS2), and other genes are activated and transcribed by interaction with bile salts within the host. Vp also has two putative type-III and type-VI secretion systems (T3SS and T6SS, respectively) located on both the chromosomes. T3SS play a crucial role during the infection process by causing cytotoxicity and enterotoxicity. T6SS contribute to adhesion, virulence associated with interbacterial competition in the gut milieu. Chromosome-1 encoded T6SS1 has been predominantly identified in clinical isolates. Acquisition of genomic islands by horizontal gene transfer provides enhanced tolerability of Vp towards several antibiotics and heavy metals. Vp consists of evolutionarily conserved targets of GTPases and kinases. Expression of these genes is responsible for the survival of Vp in the host and biochemical utilization during its survival. Advanced genomic analysis has revealed that various genes are encoded in V. parahaemolyticus-pathogenicity island that control and expression of virulence in the host. In the environment, biofilm gene expression has been positively correlated to tolerance towards aerobic, anaerobic and micro-aerobic conditions. The genetic similarity analysis of toxin/antitoxin systems of Escherichia coli with VP genome has shown a function that could induce a viable nonculturable state by inhibiting cell division. A better interpretation of the Vp virulence and other mechanisms that support its environmental fitness are important for diagnosis, treatment, prevention and spread of infections. This review aims to bring together currently available information on Vp adaptation to different niches.